A Grandiosa Obra de Santo Antonio (Redaccao da Voz de Santo Antonio, 1901)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

A Grandiosa Obra de Santo Antonio (Redaccao da Voz de Santo Antonio, 1901)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 6.Yellowing 變黃

Annaes da Obra da Santa- Infancia (Typ. Da Casa Catholica, 1901)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Annales des Franciscaines Missionnaires de Marie (Imp. Franc. Missionn, 1901)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Boletim Official do Governo da Provincia de Macau (IMPRENSA NACIONAL, 1901)
Stamp of St. Joseph Seminary
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

compendium theologiae dogmaticae (Typis Societatis Missionum Ad Exteros, 1901)
sign, stamp of seminario diocesano de Macao
Keywords: 18.Bookworm; Fair

O dia de S. Lamecha: comedia em 1 acto (Tavares Cardoso, 1901)
Keywords: Condition: Fair; Literature

Un Aide Dans La Douleur (Ancienne Maison Charles Douniol, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover)

Vieira- Pregador (Editor, José Fructuoso da Fonseca, 1901)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Vers L'Eternite - Abbe Poulin (Ancienne Maison Charles Douniol, 1901)
Keywords: Condition: Fair; Philosophy

Christo - Agostinho, Jose (Livraria Editora Antonio Figueiriha, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Manuel Biblique, Cours D'ecriture Sainte - Bacuez, MM (A. Roger et F. Chernoviz, Editeurs, 1901)
Signature, Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Prince Henry the Navigator, the hero of Portugal and of modern discovery, 1394-1460 A.D.: with an account of geographical progress throughout the Middle Ages as the preparation for his work - Beazley, C. Raymond (Burt Franklin research & source works series, 1901)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Biographies; Condition: Fair; Discoveries in geography; Découvertes géographiques; Explorers; Explorers Portugal Biography; Geography, Medieval; Géographie médiévale; Hard Cover; Henry, Infante of Portugal, 1394-1460; History; Portugal; Travel; collective biographies

Saint Jean-Baptiste De La Salle - Blain, J. B (Societe de Saint Augustin, Desclee, de Brouwer et Cie, 1901)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Vieira- Pregador, Estudo Philosophico da Eloquencia Sagrada - Cabral, P. Luiz Gonzaga do Valle Coelho Pereira (Editor, José Fructuoso da Fonseca, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Vieira prégador: estudo philosophico da eloquencia sagrada : segundo a vida e as obras do grande orador portuguez - Cabral, Luiz Gonzaga do Valle Coelho Pereira (Editor, José Fructuoso da Fonseca, 1901)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Biographies; Condition: Fair; Hard Cover; Jesuits Portugal Biography; Philosophy; Portugal; Vieira, António, 1608-1697

Vieira prégador: estudo philosophico da eloquencia sagrada : segundo a vida e as obras do grande orador portuguez - Cabral, Luiz Gonzaga do Valle Coelho Pereira (Editor, José Fructuoso da Fonseca, 1901)
Keywords: 10.Cover Damage; 2.Damage; Biographies; Condition: Fair; Jesuits Portugal Biography; Philosophy; Portugal; Vieira, António, 1608-1697

Vieira prégador: estudo philosophico da eloquencia sagrada : segundo a vida e as obras do grande orador portuguez - Cabral, Luiz Gonzaga do Valle Coelho Pereira (Editor, José Fructuoso da Fonseca, 1901)
Keywords: 10.Cover Damage; 2.Damage; Biographies; Condition: Fair; Jesuits Portugal Biography; Philosophy; Portugal; Vieira, António, 1608-1697

Vieira prégador: estudo philosophico da eloquencia sagrada : segundo a vida e as obras do grande orador portuguez - Cabral, Luiz Gonzaga do Valle Coelho Pereira (Editor, José Fructuoso da Fonseca, 1901)
Keywords: 10.Cover Damage; 2.Damage; Biographies; Condition: Fair; Jesuits Portugal Biography; Philosophy; Portugal; Vieira, António, 1608-1697

Medicina Pastoralis - Capellmann, C. (Sumptibus Rudolphi Barth, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Notre- Dame de Lourdes, Recits et Mysteres - Cros, P. L. Jos.- Marie (Victor Retaux, 1901)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

A Alma aos Pes de Maria - d'Araujo, Jose Goncalves Cascao (Livraria Povoense- Editora, 1901)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Le Deboir du Chretien dans les Jours D'epreuve et de combat - Daniel, P. Ch. (Ancienne Maison Douniol, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover)

A Alma Aos Pes de Maria Santissima a Arvore da Vida - Filippo, Joao (Aloysio Gomes da Silva, Editor, 1901)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm (Only Cover)

Saint Yves - Fonciere, Ch. de La (1901)
Keywords: 1.Conservation 保護; 2.Damage

Luctas da Penna - Freitas, Senna (Typographia Universal, 1901)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Le Saint SAcrifice de la Messe - Gihr, Nicolas (P. Lethielleux, Libraire-Editeur, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Cursus Scripturae Sacrae, Commentarius in Deuteronomium - Hummelauer, Francisco de (Sumptibus P. Lethielleux, Editoris, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Summa Theologica - Janssens, Laurentio (1901)
Keywords: 1.Conservation 保護; 2.Damage

Tractatus de Deo-Homine sive de Verbo Incarnato - Janssens, Laurentio (Sumptibus Herder, 1901)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Retraites Pascales 1872-1873-1874 - Le T. R. P. J.-L.-M. Monsabre (P. Lethielleux, 1901)
stamp of biblotheque de Nazareth
Keywords: Good

Retraites Pascales 1875-1876 - Le T. R. P. J.-L.-M. Monsabre (P. Lethielleux, 1901)
stamp of biblotheque de Nazareth
Keywords: Good

Sainte Genevieve - Lesetre, Henri (Librairie Victor Lecoffre, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Meditations: a l'usage du clerge et des fides pour tous les jours de l'annee - M. Hamon (Librairie Victor Lecoffre, 1901)
Keywords: 18.Bookworm (Only Cover); 22.signature; Condition: Fair; Hard Cover; Religion

A Bulla da Santa Cruzada - Mattoso, Jose Alves (Imprensa Academica, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

Institutiones Philosophiae scholasticae ad mentem Divi Thomae ac Suarezü - Mendive, José (Typis Joseph Baamonde a Cuesta, 1901)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Cloth bindings (Binding); Condition: Fair; Gold tooled bindings (Binding); Hard Cover; Machine-made papers (Paper); Philosophy; Scholasticism; Scolastique; Wove papers (Paper); scholasticism

Compendio de Theologia Gogmatica Especial Segundo a Mente de S. Thomaz D'Aquino - Miguel Ferreira d'Ollmeida (Typographia da Revista Catholica, 1901)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Compendio de Theologia Gogmatica Especial Segundo a Mente de S. Thomaz D'Aquino - Miguel Ferreira d'Ollmeida (Typographia da Revista Catholica, 1901)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Compendio de Theologia Gogmatica Especial Segundo a Mente de S. Thomaz D'Aquino - Miguel Ferreira d'Ollmeida (Typographia da Revista Catholica, 1901)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Vieira-Prègador : Estudo Filosófico da Eloqüência Sagrada segundo a vida e as Obras do Grande Orador Portuguêz - P. Luís Gonzaga Cabral (Jose Fructuoso Da Fonseca, 1901)
stamp of "seminario de s. jose Macau"
Keywords: Good

Santa Lydwina de Schiedam - Pereira, B da Costa (Livraria Povoense- Editora, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing

Meditations sur Les Sept Paroles de N. S. Jesus- Christ en Croix - Perraud, L'Abbe Charles (Ancienne Maison Charles Douniol, 1901)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm (Only Cover)

Apologetica - Santanna. M Fernandes (Typographia da Casa Catholica, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

A Utopia Social e a Democracia Christa - Santos, Gomes dos (Typ. Adolpho de Mendonca, 1901)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Compendio de Theologia Dogmatica - Tanquerey, S. S. (Typ. da Revista Catholica, 1901)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Grammática histórica da língua portuguêsa (VI e VII classes do curso dos lyceus) - Vasconcelos, António de (Aillaud, Alves, 1901)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Portugais (Langue) Grammaire; Portuguese language Grammar; languages

Grammática histórica da língua portuguêsa (VI e VII classes do curso dos lyceus) - Vasconcelos, António de (Aillaud, Alves, 1901)
Keywords: Portugais (Langue) Grammaire; Portuguese language Grammar